The Politics of the Provisional : Art and Ephemera in Revolutionary France - Taws, Richard, 1977- (Book collections on Project MUSE., 2013)
"Examines how ephemeral images and objects made in 1790s France mediated the memory of the French Revolution and enabled new forms of political subjectivity"--Provided by publisher.